Clinical and Molecular Description of a High-Copy IncQ1 KPC-2 Plasmid Harbored by the International ST15 Klebsiella pneumoniae Clone - Willames M. B. S. Martins (American Society for Microbiology, 2020)
ABSTRACT This study provides the genomic characterization and clinical description of bloodstream infections (BSI) cases due to ST15 KPC-2 producer Klebsiella pneumoniae. Six KPC-K. pneumoniae isolates were recovered in 2015 in a tertiary Brazilian hospital and were analyzed by whole-genome sequencing (WGS) (Illumina MiSeq short reads). Of these, two isolates were further analyzed by Nanopore MinION sequencing, allowing complete chromosome and plasmid circularization (hybrid assembly), using Unicycler software. The clinical analysis showed that the 30-day overall mortality for these BSI cases was high (83%). The isolates exhibited meropenem resistance (MICs, 32 to 128 mg/liter), with 3/6 isolates resistant to polymyxin B. The conjugative properties of the blaKPC-2 plasmid and its copy number were assessed by standard conjugation experiments and sequence copy number analysis. We identified in all six isolates a small (8.3-kb), high-copy-number (20 copies/cell) non-self-conjugative IncQ plasmid harboring blaKPC-2 in a non-Tn4401 transposon. This plasmid backbone was previously reported to harbor blaKPC-2 only in Brazil, and it could be comobilized at a high frequency (10−4) into Escherichia coli J53 and into several high-risk K. pneumoniae clones (ST258, ST15, and ST101) by a common IncL/M helper plasmid, suggesting the potential of international spread. This study thus identified the international K. pneumoniae ST15 clone as a carrier of blaKPC-2 in a high-copy-number IncQ1 plasmid that is easily transmissible among other common Klebsiella strains. This finding is of concern since IncQ1 plasmids are efficient antimicrobial resistance determinant carriers across Gram-negative species. The spread of such carbapenemase-encoding IncQ1 plasmids should therefore be closely monitored. IMPORTANCE In many parts of the world, carbapenem resistance is a serious public health concern. In Brazil, carbapenem resistance in Enterobacterales is mostly driven by the dissemination of KPC-2-producing K. pneumoniae clones. Despite being endemic in this country, only a few reports providing both clinical and genomic data are available in Brazil, which limit the understanding of the real clinical impact caused by the dissemination of different clones carrying blaKPC-2 in Brazilian hospitals. Although several of these KPC-2-producer K. pneumoniae isolates belong to the clonal complex 258 and carry Tn4401 transposons located on large plasmids, a concomitant emergence and silent dissemination of small high-copy-number blaKPC-2 plasmids are of importance, as described in this study. Our data identify a small high-copy-number IncQ1 KPC plasmid, its clinical relevance, and the potential for conjugative transfer into several K. pneumoniae isolates, belonging to different international lineages, such as ST258, ST101, and ST15.